Ferrite-based soft and hard magnetic structures by extrusion free-forming. Issue 43 (22nd May 2017) - Peng, Erwin; Wei, Xiangxia; Herng, Tun Seng; Garbe, Ulf; Yu, Dehong; Ding, Jun
Abstract : Simple fabrication of a ferrite-based bulk soft magnet (NiFe2 O4 ) and hard magnet (BaFe12 O19 ) using the extrusion free-forming process. Abstract : Functional ceramic materials, especially those with unique magnetic properties, with complex geometries have become increasingly important for various key technologies in industry. Herein, ferrite-based soft (NiFe2 O4 ) and hard (BaFe12 O19 ) bulk magnetic structures with three-dimensional morphologies are successfully fabricated from inexpensive metal oxide powder (NiO/Fe2 O3 and BaCO3 /Fe2 O3 ) precursors through a simple extrusion free-forming (EFF) technique coupled with a high temperature solid-state reaction process. Dense polycrystalline microstructures with negligible porosity are observed for samples sintered above 1200 °C and highly crystalline NiFe2 O4 and BaFe12 O19 phases are successfully formed. The printed structures also exhibit either soft or hard magnetic material behavior with (i) saturation magnetization values up to approximately 86% and 95% of the NiFe2 O4 and BaFe12 O19 theoretical bulk magnetization values, respectively, and (ii) high densities up to ∼93% of their respective theoretical bulk density. Bulk magnetic structures with unique geometries ( e.g. mesh, gear, ring and cylinder) are successfully fabricated. The EFF technique demonstrated in this work can be readily extended to other functional ferrite or titanate ceramic materials simply by changing the metal oxide powder precursors.